SENSORY PROFILE OF ARABICA COFFEE ACCESSES OF THE GERMPLASM COLLECTION OF MINAS GERAIS – BRAZIL - Fassio, Larissa de Oliveira; Pereira, Rosemary Gualberto Fonseca Alvarenga; Malta, Marcelo Ribeiro; Liska, Gilberto Rodrigues; Sousa, Maisa Mancini Matioli; Carvalho, Gladyston Rodrigues; Pereira, Antonio Alves (Coffee Science - ISSN 1984-3909, 2019)
This study was developed to determine the beverage quality and the sensory profile of Coffea arabica accesses of the Germplasm Collection of Minas Gerais State in two consecutive harvests. Mature coffee fruits from 49 accesses were selectively harvested in the 2015 and 2016 harvests, and after processing and drying they were sensorially evaluated by a team of trained judges in accordance to the protocols of the Specialty Coffee Association. The data were analyzed by Principal Component Analysis, Cluster Hierarchical Analysis, and Content Analysis. The year of harvest influences the scores of the sensory attributes of the beverage of some coffee accesses. The access 27 (Pacamara) stood out with the highest sensory score seen in the first year of harvest. The accesses 36 (Timor Hybrid UFV376-52) and 43 (BE5 WushWush) stood out for the final sensory score in the two years of evaluation. All accesses belonging to the Timor Hybrid Germplasm stood out in the beverage quality in the second year of harvest. A total of 139 sensory attribute descriptors were identified, and the content analysis showed different levels for the frequency of terms in each access group formed as a function of quality. The Germplasm Collection of Minas Gerais has a wide variability for the production of superior quality coffees, and the year of harvest influences to a greater or lesser degree the potential of quality of the accesses.